Dermatophytes in Cats without Dermatopathies in the Metropolitan Area of Florianópolis, Brazil - Fraga, Cibele Floriano; Spanamberg, Andréia; Ferreiro, Laerte; Silva, Gisele Alabora da; Francheschi, Natália Tomazi; Silva, Isabel Tomazi da; Vargas, Raisa Chacon de (Acta Scientiae Veterinariae, 2017)
Background: Dermatophytes are infectious agents responsible for dermatophytosis, an important worldwide zoonosis. Cats are considered potential hosts and reservoir of these fungi, especially Microsporum canis. The prevalence in cats without dermatopathies varies according to the region, climate and animal husbandry. The aim of this study was to estimate the frequency of dermatophytes in cats without clinical signs of dermatopathy in the Metropolitan Area of Florianópolis, situated in the coast of Southern Brazil. Materials, Methods & Results: A total of 198 samples were obtained from cats without dermatopathies domiciled in the metropolitan area of Florianópolis. The collections were made through vigorous hair brushing throughout the body of the animal, using a sterile toothbrush. Mycological culture was performed onto Sabouraud Agar Chloramphenicol-Cyclohexamide (SCC), and incubated at 25-27°C for 21-28 days. The diagnosis was based on the macro and micromorphological characteristics of the isolated dermatophyte. One hundred and ten samples (55.6%) were collected in veterinary clinics and 88 (44.4%) in multiple household cats (average 11). The frequency of dermatophytes corresponded to 3.0% (6/198). Only the genus Microsporum was observed with predominance of M. canis (66.7%), followed by M. gypseum (33.3%). Saprotrophic fungi were observed in 94.4% of the cultures and 5.6% of the samples did not occurred fungal growth. Most of the isolates were obtained from adult cats (66.7%), females (83.3%) and with long hair (5.4%) in comparison to short hair samples (2.1%). Thirty percent of the cats (59/198) had been tested for retroviruses, and, among them, 27.0% were positive (22% FeLV and 5% FIV). M. gypseum was isolated from one feline FeLV positive. Various saprotrophic species were isolated from multiple household cats. Discussion: Dermatophytosis is considered as the most common occupational zoonosis among veterinarians, and it is recognized as a biological risk associated to the direct contact with cats. There are reports of regional outbreaks in Brazil where the pets were indicated as sources of dermatophytes to humans in the domestic environment. The frequency of dermatophytes observed in this study (3.0%) was lower than shown in others papers. Microsporum canis is commonly isolated from cats in hot weather regions and crowded living facilities; once introduced in to the creation on a cattery it is difficult to be eliminated. There is evidence of a higher occurrence of M. canis in cats FIV positive than seronegative ones. Dermatophytes were isolated from cats in contact with other cats (5/165). However, multiple household cats had no positive cultures and this outcome can be associated to high contamination by saprotrophic fungi. For diagnosis of dermatophytosis, mycological culture is indicated as the most efficient and easy to perform method, but it is necessary to be aware of false negative results, since it can occur in situations of intense contamination. Thus, it is advisable to prophylactically perform a clinical examination as a routine and also laboratory analyses in each cat before introducing it to a new environment.